2017
DOI: 10.1080/00343404.2017.1282609
|View full text |Cite
|
Sign up to set email alerts
|

Waving goodbye? The determinants of autonomism and secessionism in Western Europe

Abstract: This paper sheds light on the main aggregate-level determinants of electoral support for regionalist parties across 10 Western European countries. A region being relatively richer than the country to which it belongs is associated with higher electoral support for regionalist parties only to the extent that the region is culturally differentiated. This hypothesis is substantiated theoretically, tested empirically and found to hold in the form of a strong and significant interaction effect between cultural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…While nearly 50 percent of all states have been confronted by ethno-national movements in the last decades (Connor 1994(Connor , 2001, little systematic evidence has explored the social bases of the national quests (some exceptions notwithstanding, e.g. Álvarez Pereira et al 2018;Massetti & Schakel 2016;Burg 2015;Muñoz & Tormos 2015;Sorens 2005). We contend that the concern for the class base of political conflict should expand beyond the anti-austerity protest domain to encompass popular mobilisations in a wide array of arenas, including the recent upsurges of secessionist movements that unfolded under meagre economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…While nearly 50 percent of all states have been confronted by ethno-national movements in the last decades (Connor 1994(Connor , 2001, little systematic evidence has explored the social bases of the national quests (some exceptions notwithstanding, e.g. Álvarez Pereira et al 2018;Massetti & Schakel 2016;Burg 2015;Muñoz & Tormos 2015;Sorens 2005). We contend that the concern for the class base of political conflict should expand beyond the anti-austerity protest domain to encompass popular mobilisations in a wide array of arenas, including the recent upsurges of secessionist movements that unfolded under meagre economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…A country C is geographically partitioned into R(C) subnational regions, indexed by r. There are N (C) individuals, partitioned into L identity groups, indexed by or k. Denote by N ( , r, C) the number of individuals of group living in region r of country C. Income per capita differs across regions but not within regions. 6 Denote by y(r, C) the income per capita of an individual who resides in region r of country C, and by Y (C) the total income in country C.…”
Section: Setupmentioning
confidence: 99%
“…Race, gender and religion also constitute important identity cleavages(Desmet and Wacziarg, 2021). In recent decades, these cleavages have contributed to the rise of identity politics in many advanced democracies(Fukuyama, 2018; Bonomi, Gennaioli and Tabellini, 2021; Gethin, Martínez-Toledano and Piketty, 2021) 6. Allowing for income differences within regions is a straightforward extension.…”
mentioning
confidence: 99%
“…In addition, most scholars have shown that identity and ethnic divisions are important preconditions for the development of secessionist movements (Bond, 2000), although this relationship is complex and multifaceted (Blais et al, 1992;McCrone & Paterson, 2002;Serrano, 2013). Hence, economic variables only seem to be relevant for pro-secessionist parties when linguistic divisions are involved as well (Álvarez Pereira et al, 2018). In the same vein, political decentralization may incentivize demands for self-government where ethnic divisions are politically relevant (Brancati, 2006;Massetti & Schakel, 2013).…”
Section: The Role Of Parties In Increasing Demands For Secessionmentioning
confidence: 99%